Learning based on teacher projects and self-efficacy when formulating a class curriculum - Enrique Caballero Barros; Carlos Briones Galarza; Jorge Flores Herrera (Universidad Politécnica Salesiana, 2014)
The purpose of this study was to improve the performance and to determine the change in selfefficacy of students in formulating a lesson plan during the implementation of project-based learning (PBL). In this study participated 17 students, registered in the course of Simulation of Experiments in Physics. Students in this graduate course work as physics teachers at the secondary level. The instructional task selected was the formulation of a lesson plan. The time devoted to the teaching of this content was 24 hours. At the start of the course they were asked to develop a lesson plan. Then, the students before and after the implementation of PBL were administered the self-efficacy questionnaire consisting of 15 items. The results show that students improved their performance and changed their perception of self-efficacy in the development of a lesson plan and the PBL was part of that achievement.